2010
DOI: 10.1017/s1462399410001602
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights into amyloid regulation by membrane cholesterol and sphingolipids: common mechanisms in neurodegenerative diseases

Abstract: Alzheimer, Parkinson and other neurodegenerative diseases involve a series of brain proteins, referred to as ‘amyloidogenic proteins’, with exceptional conformational plasticity and a high propensity for self-aggregation. Although the mechanisms by which amyloidogenic proteins kill neural cells are not fully understood, a common feature is the concentration of unstructured amyloidogenic monomers on bidimensional membrane lattices. Membrane-bound monomers underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
177
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(187 citation statements)
references
References 149 publications
(235 reference statements)
5
177
1
4
Order By: Relevance
“…Mechanistic studies with well defined model membranes have shown that natively unfolded polypeptides, upon interaction with surfaces, readily adopt helical structures that represent key intermediates in amyloid formation process (Abedini & Raleigh, 2009). In particular, anionic surfaces and anionic phospholipid-rich membranes can play key roles either in triggering protein fibrillogenesis by acting as conformational catalysts for amyloid fibrils deposition (Fantini & Yahi, 2010), or as inhibitors of fibrillogenesis (Zhu & Fink, 2003). We demonstrated that the conformation of the fibrillogenic polypeptide [1-93]ApoA-I is largely affected by membrane-mimicking structures, such as liposomes (Monti et al, 2010).…”
Section: Effects Of Liposomes On [1-93]apoa-i Aggregationmentioning
confidence: 96%
See 2 more Smart Citations
“…Mechanistic studies with well defined model membranes have shown that natively unfolded polypeptides, upon interaction with surfaces, readily adopt helical structures that represent key intermediates in amyloid formation process (Abedini & Raleigh, 2009). In particular, anionic surfaces and anionic phospholipid-rich membranes can play key roles either in triggering protein fibrillogenesis by acting as conformational catalysts for amyloid fibrils deposition (Fantini & Yahi, 2010), or as inhibitors of fibrillogenesis (Zhu & Fink, 2003). We demonstrated that the conformation of the fibrillogenic polypeptide [1-93]ApoA-I is largely affected by membrane-mimicking structures, such as liposomes (Monti et al, 2010).…”
Section: Effects Of Liposomes On [1-93]apoa-i Aggregationmentioning
confidence: 96%
“…The general concept that biological surfaces may influence and direct molecular assemblies is gaining increasing attention. It is known that the interaction of natively folded proteins with groups exposed on a membrane surface often modifies their conformational states (Fantini & Yahi, 2010;Shanmugam & Jayakumar, 2004;Kakio et al, 2004). On the other hand, unfolded polypeptide chains can gain ordered structures at the membrane surface or inside the bilayer (Fantini & Yahi, 2010).…”
Section: Extrinsic Factors That Influence Amyloid Formation: Effects mentioning
confidence: 99%
See 1 more Smart Citation
“…Эти результаты согласуются с экспериментальными данными (см., например, обзор [35]), свидетельствующими о том, что важным фактором, обеспечивающим энергетическую стабилизацию комплексов β-GalCer с белками, являются XH···π водородные связи остатка сахара с ароматическими аминокислотами. В частности, исследования -амилоидного и PrP пептидов, использующих β-GalCer для проникновения в клетку-мишень, показали [36,37], что ключевую роль в связывании играют XH···π взаимодействия углеводной части гликолипида с остатками их ароматических аминокислот.…”
Section: результаты и их обсуждениеunclassified
“…3), определяет специфичность их связывания с белком gp120 ВИЧ-1. Правомерность этого предположения подтверждает тот факт, что остаток жирной кислоты молекулы β-GalCer, с помощью которой вирус внедряется в некоторые чувствительные клетки, отличные от макрофагов и Т-лимфоцитов [9,10], погружен вглубь мембраны, а наиболее доступным элементом структуры гликолипида является пиранозное кольцо галактозы [35]. О важном вкладе остатка галактозы -GalCer в Примечания: а Аминокислотные остатки петли V3, образующие π-стэкинг с ароматическими фрагментами боковых цепей гликолипидов группы I; б Аминокислотные остатки петли V3, участвующие в XH···π взаимодействиях с пиранозным кольцом галактозы гликолипидов; в Межмолекулярные водородные связи.…”
Section: результаты и их обсуждениеunclassified